Pengaruh Pendapatan dan Literasi Keuangan terhadap Penggunaan E-Wallet pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret - Nada Indie Kharisma; Salman Alfarisy Totalia; Dini Octoria (Journal on Education, 2024)
This study aims to determine the effect of income and financial literacy on the use of e-wallets on students of the Faculty of Teacher Training and Education, Sebelas Maret University. The sampling technique in this study used non-probability sampling, namely purposive sampling with a sample of 271 respondents. The validity and reliability test techniques used are Pearson Product Moment and Cronbach Alpha. The research method used is descriptive quantitative. The data analysis technique used in this research is descriptive statistical analysis and multiple linear regression analysis. The results of this study found that: (1) Income has a positive and significant influence on the use of e-wallets on FKIP UNS students with a t test value, namely, t count 6.432> 1.986 (t table) and significance 0.000 <0.05. (2) Financial literacy has a positive and significant effect on the use of e-wallets in FKIP UNS students with a t test value, namely, t count 11.467> 1.986 (t table) and a significance of 0.000 <0.05. (3) Income and financial literacy have a simultaneous influence on the use of e-wallets in FKIP UNS students with a significance of 0.000 <0.05.